Evaluación del índice verde urbano de la parroquia Calceta para la elaboración de un plan de manejo de áreas verdes - Cusme Sacón, María Dolores (2022)
The objective of this research was to evaluate the urban green index (IVU) in Calceta parish, for the elaboration of a management plan for green areas. The IVU was determined through a documentary and bibliographic review of the cantonal GAD databases, and the quantification of existing green areas using scientific observation, obtaining a total of 14 green areas divided into parks and flower beds. With the total surface of the green areas and the population, the urban green index was calculated, which presented a value of 0.9 m2/inhabitant; and finally, the diversity of species in the identified areas was assessed using the Simpson and Shannon-Wiener indices, obtaining a total of 19 native species and 12 introduced species with medium diversity and high dominance. Subsequently, a socioeconomic and environmental analysis of the urban green areas identified was carried out by applying a survey to the inhabitants in Calceta and calculating the importance index through the use of weighted social, economic and environmental variables; it was concluded that none of the urban green areas has a high rating, which shows that due attention has not been given to the comprehensive management, maintenance and good condition of these areas. With the results obtained, a management plan for green areas was developed, which was socialized with representatives of the Decentralized Autonomous Government in Bolívar canton.